A detailed investigation of ambient aerosol composition and size distribution in an urban atmosphere - Kuzu, S. Levent; Saral, Arslan; Demir, Selami; Summak, Gulsum; Demir, Goksel (SPRINGER HEIDELBERG, 2013)
This research was executed between March 2009 and March 2010 to monitor particulate matter size distribution and its composition in Istanbul. Particulate matter composition was determined using ion chromatography and inductively coupled plasma optical emission spectrometry. The sampling point is adjacent to a crowded road and the Bosporus Strait. Two prevailing particulate modes are found throughout PM10 by sampling with a nine-stage low-volume cascade impactor. First mode in the fine mode is found to be between 0.43 and 0.65 mu m, whereas the other peak was observed between 3.3 and 4.7 mu m, referring to the coarse mode. The mean PM10 concentration was determined as 41.2 mu g/m(3), with a standard deviation of 16.92 mu g/m(3). PM0.43 had the highest mean concentration value of 10.67 mu g/m(3), making up nearly one fourth of the total PM10 mass. For determining the effect of traffic on particulate matter (PM) composition and distribution, four different sampling cycles were applied: entire day, nighttime, rush hour, and rush hour at weekdays. SO (4) (-2) and organic carbon/elemental carbon proportions are found to be lower in night samples, representing a decrease in traffic. The long-range transports of dust storms were observed during the sampling periods. Their effects were determined analytically and their route models were run by the HYSPLIT model and validated through satellite photographs taken by the NASA Earth Observatory.
Keywords: Particulate matter; Size distribution; Ion and elemental composition; Long-range transport; TRACE-ELEMENTS; PARTICLES; TRANSPORT; HEALTH; METALS; STREET; DUST; AREA; AIR; Environmental Sciences & Ecology